A Case of Identity: The Artefacts of the 1770 Kamay (Botany Bay) Encounter*. Issue 1 (2nd January 2018) - Thomas, Nicholas
Abstract : Collections of Indigenous artefacts made during the voyages of Captain James Cook have been extensively researched, but significant issues around the provenance and identification of artefacts remain complex and unresolved. This article considers the case of a shield in the British Museum, said for fifty years to have been appropriated by Cook at the time of first contacts with Gweagal in April 1770, and other artefacts associated with the same encounters.